MIL-101(Cr)-Functionalized TEDA-BAIL: An Efficient and Recyclable Catalyst for the Synthesis of Pyrimido[4,5-b]quinolinetrione Derivatives - Mahmoudi, Zohreh; Kabirifard, Hassan; Ghasemzadeh, Mohammad A. (Current Organocatalysis, 2023)
Background: In this study, a heterogeneous catalyst containing MIL-101(Cr) functionalized TEDA-BAIL was used to carry out an efficient four-component reaction between aromatic aldehydes, barbituric acid, dimedone, and aryl amines, resulting in the synthesis of a new class of pyrimido[4,5-b]quinolinetrione derivatives. Methods: Pyrimido[4,5-b]quinolinetrione derivatives were synthesized through a one-pot fourcomponent reaction between aromatic aldehydes, barbituric acid, dimedone, and aryl amines, in the presence of triethylenediamine-based ionic liquid@MIL-101(Cr) composite as a catalyst under reflux conditions. The TEDA-BAIL@MIL-101(Cr), which is a recyclable catalyst, was fully characterized by Fourier transform infrared spectrophotometry (FT-IR), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX) thermogravimetric analysis (TGA), Brunauer-Emmett-Teller (BET) and Transmission electron microscopy (TEM). Results: Four-component synthesis of pyrimido[4,5-b]quinolinetriones was catalyzed by TEDABAIL@ MIL-101(Cr) with aromatic aldehydes, barbituric acid, dimedone, and aryl amines under reflux conditions. The obtained experimental results revealed that the employed synthesis approach is a simple method that offers several advantages, including sustainability, facile separation from the reaction medium, and reusability of the catalyst after six consecutive runs without loss of activity. Conclusion: The presented method is an efficient synthesis route for the synthesis of pyrimido[4,5- b]quinolinetriones in the presence of TEDA-BAIL@MIL-101(Cr) under reflux conditions. This procedure provides multiple advantages, such as ease of execution, high yield, clean reaction conditions, shorter reaction time, and catalyst sustainability.
Keywords: Multicomponent reaction